Il giornalista : Edgardo Pellegrini, cronista del mondo : articoli, immagini, ricordi. - Fracassi, Claudio; Lucas, Uliano; Deiana, Elettra; Pellegrini, Edgardo (Roma : I Libri del Altritalia.)
Bibliotheek François Vercammen
Italiaans
Monografie